Linguistics and Literary Studies / Interfaces, Encounters, Transfers / Begegnungen, Interferenzen und Kooperationen. - Fludernik, Monika (Linguae & litterae., 2014)
This volume explores the interface between linguistics and literary studies. Theoretical and textual analyses help illustrate the common features between everyday discourse and literature, and show the potentials for a collaborative approach between literary scholars and linguists in understanding speech acts and reference; inference, cognitive and cultural background; rhetoric, styles of speaking and writing; as well as perspectives and genres.